Burden of cancer in the Eastern Mediterranean Region, 2005-2015: findings from the Global Burden of Disease 2015 Study - Fitzmaurice, Christina; Jonas, Jost B.; Mohammed, Shafiu (International journal of public health, 2018)
To estimate incidence, mortality, and disability-adjusted life years (DALYs) caused by cancer in the Eastern Mediterranean Region (EMR) between 2005 and 2015.
Gesehen am 03.09.2020
Published online: 3 August 2017
GBD 2015 Eastern Mediterranean Region Cancer Collaborators*: Fitzmaurice, Christina, Jost B.Jonas, Shafiu Mohammed [und viele weitere]